An Overview of Franchising In The Hospitality Industry - Ersan Suria Pranoto (Binus Business Review, 2010)
Nowadays, franchising is the most significant part in the hospitality industry through hotels and fast food restaurant. Franchisor gives the right to the franchisee to sell their product and service also to sub franchise it and worked under their brand name. Furthermore, in franchising there must be a contract between the franchisor and the franchisee which include the term and condition. Franchises include some aspects such as, screening, site selection, operating manuals and the pre opening. However, there are some advantages and disadvantages for both the franchisor and the franchisee. The expansion of franchise can be achieved through different strategies of distribution and the knowledge of the targeted market. The future of franchise can be gained through strategies of distribution system, which could emerge the entrepreneur into the majority economy and business.